Signaling pathway mechanisms of circadian clock gene Bmal1 regulating bone and cartilage metabolism: a review - Yiting Ze; Yongyao Wu; Zhen Tan; Rui Li; Rong Li; Wenzhen Gao; Qing Zhao (Bone Research)
Abstract Circadian rhythm is ubiquitous in nature. Circadian clock genes such as Bmal1 and Clock form a multi-level transcription-translation feedback network, and regulate a variety of physiological and pathological processes, including bone and cartilage metabolism. Deletion of the core clock gene Bmal1 leads to pathological bone alterations, while the phenotypes are not consistent. Studies have shown that multiple signaling pathways are involved in the process of Bmal1 regulating bone and cartilage metabolism, but the exact regulatory mechanisms remain unclear. This paper reviews the signaling pathways by which Bmal1 regulates bone/cartilage metabolism, the upstream regulatory factors that control Bmal1, and the current Bmal1 knockout mouse models for research. We hope to provide new insights for the prevention and treatment of bone/cartilage diseases related to circadian rhythms.